The Overview of Coronary Heart Disease Risk Factors in Perimenopausal and Postmenopausal Female Patients at Haji Adam Malik General Hospital in 2021 - Faustine, Elaine; Andra, Cut Aryfa; Dalimunthe, Dina Arwina; Haykal, Teuku Bob; Andriyani, Yunilda (Talenta Publisher, 2023)
ABSTRACT Background: Cardiovascular diseases are taking an estimated 17, 9 million lives each year, 85% were caused by coronary heart disease. After menopause, there are physiological changes that occurs in womenâ€™s body that increase the risk of coronary heart disease. Risk factors associated with the incidence of coronary heart disease are, family history, age, hypertension, diabetes, dyslipidemia, obesity, and smoking. Objectives: To examine the risk factors associated with the incidence of coronary heart disease in perimenopausal and postmenopausal women at RSUP Haji Adam Malik in 2021. Methods: This study is a descriptive study with cross sectional design and retrospective approach, carried out at RSUP Haji Adam Malik. The data were taken from 1 January-31 December 2021. Results: The results showed that out of 75 perimenopausal and postmenopausal women who suffered from CHD, 61 patients (81,3%) were >50 years old, 3 patients (4%) had a family history of CHD, 53 patients (70,7%) had hypertension, 45 patients (60%) had diabetes, 58 patients (77,3%) with dyslipidemia, 10 patients (13,3%) were obese, and 14 patients (18,7%) had a history of smoking. Conclusion: Risk factors for CHD in perimenopausal and postmenopausal women, are having a family history of CHD, age, hypertension, diabetes, dyslipidemia, obesity, and smoking. Keywords: coronary heart disease, risk factors, perimenopausal women, postmenopausal women, women with CHD Â ABSTRAK Latar Belakang: Penyakit kardiovaskular menyebabkan kematian 17,9 juta penduduk dunia setiap tahunnya, dan 85% diantaranya disebabkan oleh penyakit jantung koroner. Pada wanita yang telah mengalami menopause, terjadi perubahan fisiologis pada tubuh wanita sehingga risiko penyakit jantung koroner meningkat. Faktor risiko yang meningkatkan kejadian penyakit jantung koroner antara lain, usia, riwayat keluarga, hipertensi, diabetes, dislipidemia, obesitas, dan merokok. Tujuan: Untuk mengetahui faktor risiko yang menyebabkan terjadinya penyakit jantung koroner pada pasien wanita perimenopause dan postmenopause di RSUP Haji Adam Malik Medan pada tahun 2021. Metode: Jenis penelitian yang dilakukan adalah penelitian deskriptif dengan desain penelitian cross sectional dengan pendekatan retrospektif, yang dilakukan di RSUP H. Adam Malik. Hasil: Hasil penelitian menunjukkan, dari 75 orang wanita perimenopause dan postmenopause yang menderita PJK, sebanyak 61 pasien (81,3%) berusia >50 tahun, 3 pasien (4%) memiliki riwayat keluarga dengan PJK, 53 pasien (70,7%) menderita hipertensi, 45 pasien (60%) menderita diabetes, 58 pasien (77,3%) mengalami dislipidemia, 10 pasien (13,3%) mengalami obesitas, dan 14 pasien (18,7%) memiliki riwayat merokok. Kesimpulan: Faktor risiko PJK pada wanita perimenopause dan postmenopause, meliputi riwayat keluarga, usia, hipertensi, diabetes, dislipidemia, obesitas, dan merokok. Kata Kunci: faktor risiko, penyakit jantung koroner, wanita dengan PJK, wanita perimenopause, wanita postmenopause